Why Is There No Labor Party in the United States? Political Articulation and the Canadian Comparison, 1932 to 1948 - Eidlin, Barry (American Sociological Review, 2016)
Why is there no labor party in the United States? This question has had deep implications for U.S. politics and social policy. Existing explanations use “reflection” models of parties, whereby parties reflect preexisting cleavages or institutional arrangements. But a comparison with Canada, whose political terrain was supposedly more favorable to labor parties, challenges reflection models. Newly compiled electoral data show that underlying social structures and institutions did not affect labor party support as expected: support was similar in both countries prior to the 1930s, then diverged. To explain this, I propose a modified “articulation” model of parties, emphasizing parties’ role in assembling and naturalizing political coalitions within structural constraints. In both cases, ruling party responses to labor and agrarian unrest during the Great Depression determined which among a range of possible political alliances actually emerged. In the United States, FDR used the crisis to mobilize new constituencies. Rhetorical appeals to the “forgotten man” and policy reforms absorbed some farmer and labor groups into the New Deal coalition and divided and excluded others, undermining labor party support. In Canada, mainstream parties excluded farmer and labor constituencies, leaving room for the Cooperative Commonwealth Federation (CCF) to organize them into a third-party coalition.